Increasing Students' Learning Motivation Through e-Student Worksheet - Anisa Dwi Elistiyaningsi; Esti Untari; Sri Kustiyah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
During the Covid-19 pandemic, it is mandatory for every education unit to implement the PJJ system. This causes various problems, including a decrease in students' learning motivation. This study aims to determine the application of e-Student Worksheet Live Worksheet in learning to increase learning motivation in Grade II elementary school students. The approach used is a qualitative approach. The type of research used in this research is Classroom Action Research (CAR). The subjects used in this study were educators and class II students at Kraton Elementary School , Kediri Regency. The data collected in this study is the data of the thematic learning implementation process using the e-Student Worksheet Live Worksheet. The results showed that the use of e-Student Worksheet Live worksheet can increase teacher activities and student activities in learning activities and can increase students' learning motivation. For teachers, teachers should make variations in learning activities. One of them is by applying learning media in the form of e-Student Worksheet Live worksheet so that students do not get bored following learning activities and can be actively involved in learning activities.